Does the Japanese Governance System Enhance Shareholder Wealth? Evidence from the Stock-Price Effects of Top Management Turnover - Kang, Jun-Koo; Shivdasani, Anil (Review of Financial Studies, 1996)
[This article examines the stock-price effects of top management turnover announcements for 432 Japanese corporations from 1985 to 1990. We find that these announcements are associated with significantly positive abnormal returns. The returns are greater when turnover is forced than when turnover represents normal succession. The stock-price effects are also significantly positive when turnover is forced and the successor is appointed from outside the firm. We find that large shareholders play an important role during outside succession. This evidence suggests that the disciplinary decisions of Japanese governance mechanisms are consistent with shareholder wealth maximization.]